2019
DOI: 10.1136/bcr-2019-230176
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous removal of a retained appendicolith causing recurrent perihepatic abscesses between the liver and diaphragm

Abstract: Many cases of appendicitis can be associated with appendicoliths. These may sometimes be lost during appendectomies and may be lodged in the body. Most of these cases lead to recurrent abscess formation, and these appendicoliths invariably need removal. Typically, this used to be done as an open surgery or laparoscopically. Here we describe the case of a transcutaneous removal of an appendicolith that was lodged between the liver and diaphragm that led to recurrent perihepatic abscess formation in a 24-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Perihepatic abscesses resulting from dropped appendicoliths are uncommon and a review of the literature has revealed 11 cases in 10 reports, including the present one ( Table 1 ) [ [6] , [7] , [8] , [9] , 11 , [15] , [16] , [17] , [18] ]. All 11 patients had appendicectomy for perforated appendicitis and presumably, the dropped appendicoliths were secondary to the perforation.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Perihepatic abscesses resulting from dropped appendicoliths are uncommon and a review of the literature has revealed 11 cases in 10 reports, including the present one ( Table 1 ) [ [6] , [7] , [8] , [9] , 11 , [15] , [16] , [17] , [18] ]. All 11 patients had appendicectomy for perforated appendicitis and presumably, the dropped appendicoliths were secondary to the perforation.…”
Section: Discussionmentioning
confidence: 85%
“…However, the appendicolith can migrate to any part of the peritoneal cavity, the muscles of the abdominal wall, and even transdiaphragmatically [1 , 2 , 12] . This migration can result in complications such as intra-abdominal abscesses [7] , hepatic abscesses [13] , intramuscular abscesses [5] , fistulae [1] , pneumonia with empyema [12] , migration to the subcutaneous tissues and delayed wound healing [1 , 14] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are often localized in the pelvis, including the para-cecal region and Morison's pouch [ 5 ]. However, Abdullah and Singh reported an appendicolith located around the liver, causing perihepatic abscesses [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%